Penganekaragaman Atraksi Wisata dan Penguatan Konservasi Warisan Budaya Tradisional FolkGames pada Pokdarwis Desa Cempaka Bumijawa - Kuncoro Bayu Prasetyo; R. Soeharso; Hany Nurpratiwi; Latif Hendro Wibisono (Politeknik Negeri Cilacap, 2026)
Village empowerment is a strategic effort as the current development paradigm emphasizes that development begins in villages. The existence of village funds and greater autonomy encourages villages to develop themselves through various creative strategies, one of which is the village tourism concept. Near the Guci hot spring tourist area in Tegal Regency, there is the Cempaka Village Tourism Awareness Group (Pokdarwis), which develops traditional culinary tourism through Pasar Slumpring. An initial survey identified several issues that need to be addressed, namely the limited variety of traditional culinary attractions offered, stagnant visitor numbers, and the claim of a traditional-based tourism concept that has not yet significantly contributed to the preservation of local culture. As a solution to these problems, this partnership community service program aims to provide advocacy and capacity strengthening for the Cempaka Village Pokdarwis to innovate in order to increase tourist visits while contributing to the preservation of local cultural heritage through the diversification of tourism attractions based on folk games. The community service activities were carried out using the Participatory Rural Appraisal (PRA) approach and an Educational Conservation Training Program on Traditional Games as Experience-Based Tourism Attractions, integrating several activities: (1) Folk Games Clinic; (2) Arrangement of Folk Games Zones; and (3) Trial implementation of folk games tourism attractions with visitors. The results of community service activities show that the approach to developing a tourist village that combines cultural-based tourism with digital marketing strategies has significant potential in increasing the attractiveness, differentiation, and sustainability of Slumpring Market as a local culture-based tourist destination.